Drought Stress Influences the Growth and Physiological Characteristics of Solanum rostratum Dunal Seedlings From Different Geographical Populations in China - Yu, Hailun; Zhao, Xueyong; Huang, Wenda; Zhan, Jin; He, Yuanzheng (Frontiers in Plant Science, 2021)
Extensive studies have shown that the success of invasive plants in large environmental gradients can be partly attributed to related factors, including phenotypic plasticity and rapid evolution. To enhance their ability to compete and invade, invasive plants often show higher morphological and physiological plasticity to adapt to different habitat conditions. In the past few decades, invasive species have expanded to some new habitats in North and Northwest China, including arid oasis agricultural zones, which are disturbed by human activities, and the ecosystem itself is very fragile. To evaluate the ecological adaptability of invasive plants widely distributed in North and Northwest China, we studied the physiological response and tolerance mechanism of different geographical populations of Solanum rostratum Dunal to different drought-stress gradients in extremely arid regions (Xinjiang population) and semi-arid regions (Inner Mongolia population). The results showed that with the aggravation of drought stress, different geographical populations of S. rostratum adopted different physiological mechanisms to resist drought stress, and the Xinjiang population was most affected by root/shoot ratio and chlorophyll fluorescence characteristics, showing higher plasticity in the net and total photosynthetic rates, while the Inner Mongolia population mainly relied on the accumulation of osmotic adjustment substances, higher leaf dry matter content, and increased malondialdehyde to cope with drought stress. Based on these results, we concluded that the physiological responses of S. rostratum invading different habitats in northern China to drought stress were significantly different. The drought resistance of the Xinjiang population was higher than that of the Inner Mongolia population. In general, S. rostratum can be widely adapted to both harsh and mild habitats through phenotypic plasticity. It is an invasive weed threatening agricultural production and ecological environment security in northern China.